2023
DOI: 10.1002/ps.7474
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine‐mediated dopamine regulates short neuropeptide F to inhibit brown planthopper feeding behavior in tobacco‐rice rotation cropping

Abstract: BACKGROUND The tobacco‐rice rotation cropping (TRRC) is an ecologically friendly system that can both alleviate soil nicotine pollution and decrease the brown planthopper (BPH, Nilaparvata lugens Stål) fitness on rice. However, few studies on this green and effective rotational cropping system have been reported. In particular, the underlying mechanisms of TRRC on the significant reduction of field pest population at the molecular level is still unknown. RESULTS Field investigation showed that BPH population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…For example, delayed or reduced reward signaling in the brain caused by high-sugar foods was evidenced to stimulate appetite in flies . Yuan et al reported that the use of exogenous DA restored the nicotine-induced DA reduction and eliminated the inhibitory effect related to feeding in brown planthoppers . Steele et al revealed that similar to drug addiction, obesity patients showed a decrease in the effective DRD2 level in the DA system, but it increased in those who underwent gastric bypass surgery .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, delayed or reduced reward signaling in the brain caused by high-sugar foods was evidenced to stimulate appetite in flies . Yuan et al reported that the use of exogenous DA restored the nicotine-induced DA reduction and eliminated the inhibitory effect related to feeding in brown planthoppers . Steele et al revealed that similar to drug addiction, obesity patients showed a decrease in the effective DRD2 level in the DA system, but it increased in those who underwent gastric bypass surgery .…”
Section: Resultsmentioning
confidence: 99%
“…55 Yuan et al reported that the use of exogenous DA restored the nicotine-induced DA reduction and eliminated the inhibitory effect related to feeding in brown planthoppers. 56 Steele et al revealed that similar to drug addiction, obesity patients showed a decrease in the effective DRD2 level in the DA system, but it increased in those who underwent gastric bypass surgery. 57 These results suggest that overeating is induced by an impaired DA signaling pathway via a compensatory mechanism.…”
Section: Transcriptomic Changes In Drd2-related Pathwaysmentioning
confidence: 99%